A three-dimensional view of structural changes caused by deactivation of fluid catalytic cracking catalysts. Issue 1 (December 2017) - Ihli, J.; Jacob, R.; Holler, M.; Guizar-Sicairos, M.; Diaz, A.; Silva, J.; Ferreira Sanchez, D.; Krumeich, F.; Grolimund, D.; Taddei, M.; Cheng, W.; Shu, Y.; et al.
Abstract Since its commercial introduction three-quarters of a century ago, fluid catalytic cracking has been one of the most important conversion processes in the petroleum industry. In this process, porous composites composed of zeolite and clay crack the heavy fractions in crude oil into transportation fuel and petrochemical feedstocks. Yet, over time the catalytic activity of these composite particles decreases. Here, we report on ptychographic tomography, diffraction, and fluorescence tomography, as well as electron microscopy measurements, which elucidate the structural changes that lead to catalyst deactivation. In combination, these measurements reveal zeolite amorphization and distinct structural changes on the particle exterior as the driving forces behind catalyst deactivation. Amorphization of zeolites, in particular, close to the particle exterior, results in a reduction of catalytic capacity. A concretion of the outermost particle layer into a dense amorphous silica–alumina shell further reduces the mass transport to the active sites within the composite. Catalyst deactivation in fluid catalytic cracking processes is unavoidably associated with structural changes. Here, the authors visualize the deactivation of zeolite catalysts by ptychography and other imaging techniques, showing pronounced amorphization of the outer layer of the catalyst particles.